2019
DOI: 10.1556/0806.47.2019.22
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exogenous Pyridoxal-5-phosphate on Seedling Growth and Development of Wheat under Salt Stress

Abstract: Salt stress is one of the major abiotic stress which severely limits plant growth and reduces crop productivity across the world. In the present study, the effects of exogenous pyridoxal-5-phosphate (vitamin B 6 , VB 6) on seedling growth and development of wheat under salt stress were investigated. The results showed that exogenous application of pyridoxal-5-phosphate (VB 6) significantly increased the RWC, biomass, the concentration of photosynthetic pigments, proline, the activities of superoxide dismutase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Enzyme encoded by this gene family catalyzes the hydrolysis of glutamine to glutamate and ammonia as part of the biosynthesis of pyridoxal 5'-phosphate [ 36 ]. It was reported that pyridoxal 5'-phosphate was an essential compound to improve salt-stress tolerance in Arabidopsis [ 37 ], wheat [ 38 ] and rice [ 39 ]. The component also responded to several stresses such as chilling, UV radiation, and drought in tobacco [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme encoded by this gene family catalyzes the hydrolysis of glutamine to glutamate and ammonia as part of the biosynthesis of pyridoxal 5'-phosphate [ 36 ]. It was reported that pyridoxal 5'-phosphate was an essential compound to improve salt-stress tolerance in Arabidopsis [ 37 ], wheat [ 38 ] and rice [ 39 ]. The component also responded to several stresses such as chilling, UV radiation, and drought in tobacco [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation was evaluated by measuring malondialdehyde content (MDA). According to the method of the previous study ( Liu et al., 2019 ), MDA content and proline (Pro) concentration were also determined with a slightly modified method.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of PAL enzyme activity was performed according to a previous study (Wang et al, 2016). The enzyme activities of POD and catalase (CAT) were measured by the increase in absorbance at 470 and 240 nm, respectively, according to the methods of Liu et al (2019). Lipid peroxidation was evaluated by measuring malondialdehyde content (MDA).…”
Section: Determination Of Lignin Content and Enzyme Activitymentioning
confidence: 99%
“…These antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD), were tested in our study. The extractions and activities of SOD, CAT and POD were determined according to Chen et al and Liu et al's method [21,22] with several modification. Frozen pericarp tissue of passion fruit was homogenized, added to 5 ml of 80% (v/v) ethanol, and then centrifuged at 12,000×g for 10 min at 4˚C, using the supernatant to determine antioxidant capacity.…”
Section: Antioxidant-and Cell Wall-related Enzyme Activity Determinationmentioning
confidence: 99%